Divided Government and Its Impact on the Performance of Legislation in the Indonesian Province of Aceh (Universitas Medan Area, 2020)
The Indonesian Province of Aceh holds a special autonomy to have a local political party that is expected to promote the peopleâ€™s interests in Aceh. In this sense, the privileged autonomy should have to have a good governance performance.Â Nevertheless, it has not yet impacted significantly the performance of legislation. After the 2017 local election, two major local political parties dominate Acehâ€™s provincial government, which discord with each other crucially that results in a divided government. This research aims to observe factors that take effect on the performance of legislation in the province of Aceh in the course of 2014 to 2018. This study employs qualitative methods. It reveals that in the legislation process, there is ineffective communication between the provincial government of Aceh and the local parliament (Dewan Perwakilan Rakyat Aceh/DPRA) to legislate a local regulation called qanun. This phenomenon is also triggered by the dispute over the parliament, which is split between two major local political parties. With ineffective communication between the government and the parliament, they did not work optimally to legislate many bills in every one-year term. Divided government leads to the vacuum or unproductivity of elements of the provincial government.